In-situ Grown SnS2 Nanosheets on rGO as an Advanced Anode Material for Lithium and Sodium Ion Batteries - Chen, Hezhang; Zhang, Bao; Zhang, Jiafeng; Yu, Wanjing; Zheng, Junchao; Ding, Zhiying; Li, Hui; Ming, Lei; Bengono, D. A. Mifounde; Chen, Shunan; Tong, Hui (Frontiers in Chemistry, 2018)
SnS2 nanosheets/reduced graphene oxide (rGO) composite was prepared by reflux condensation and hydrothermal methods. In this composite, SnS2 nanosheets in-situ grew on the surface of rGO nanosheets. The SnS2/rGO composite as anode material was investigated both in lithium ion battery (LIB) and sodium ion battery (SIB) systems. The capacity of SnS2/rGO electrode in LIB achieved 514 mAh g-1 at 1.2 A g-1 after 300 cycles. Moreover, the SnS2/rGO electrode in SIB delivered a discharge capacity of 645 mAh g-1 at 0.05 A g-1; after 100 cycles at 0.25 A g-1, the capacity retention still keep 81.2% relative to the capacity of the 6th cycle. Due to the introduction of rGO in the composite, the charge-transfer resistance became much smaller. Compared with SnS2/C electrode, SnS2/rGO electrode had higher discharge capacity and much better cycling performance.